Impact of the asset purchase programme on euro area government bond yields using market news - Roberto De Santis (European Central Bank (ECB), 2016)
Assessing the impact of the Asset Purchase Programme (APP) by the European Central Bank (ECB) on euro area sovereign yields is challenging, because the monetary policy announcement in January 2015 was already implicitly communicated to the market in the second half of 2014. Therefore, to identify the APP for the euro area, we rely upon Bloomberg news on euro area APP. The econometric results suggest that the impact of APP on euro area long-term sovereign yields is sizeable, albeit the programme was announced at a time of low fi?nancial distress. Most of the impact took place before the purchases took place with the vulnerable countries benefiting most.
Keywords: E43; E52; E58; G14; 330; APP; quantitative easing; sovereign yields